Stress-associated protein OsSAP5 regulates rice heading date through interacting with OsGF14c in rice - Zhu, Xiaobo; Chen, Min; Dong, Zhang; Liu, Yihan; Mu, Qingshan; Basit, Farwa; Liu, Jiaxin; Hu, Jin; Guan, Yajing (Frontiers in Plant Science, 2025)
Heading date, a critical agronomic trait determining rice regional adaptation and yield potential, is regulated by complex genetic networks. Although stress-associated proteins (SAPs) are well-documented mediators of abiotic stress responses, their roles in reproductive development remain poorly characterized. Here we demonstrate that stress-associated protein 5 (OsSAP5) functions as a positive regulator of heading date in rice. Loss-of-function ossap5 mutants exhibited significant heading delay under natural short day condition, accompanied by marked downregulation of florigen genes Hd3a and RFT1 and subsequent suppression of MADS-box genes in the shoot apical meristem (SAM). A similar decrease in expression of florigen genes was observed in OsGF14c overexpression lines under short day condition. The molecular and biochemical assays confirmed that OsSAP5 interacts with OsGF14c. Notably, OsSAP5 had E3 ubiquitin ligase activity and might promote the ubiquitination of OsGF14c. Therefore, OsSAP5 regulates heading date by interacting with OsGF14c under short day condition.